ECONOMIC PROBLEMS DEPICTED IN KRISHNA SOBTI'S NOVELS - Uma Devi, Khuraijam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The well-known Hindi writer Krishna Sobti has mostly depicted the middle class of the society in her novels. Which includes both the upper middle class and the middle class. The middle class strives to improve the economic condition of its family and struggles with economic struggle along with its mental struggle. Its aspirations are to reach the upper class, for which it is always struggling. Conflict is born from inequality and the inequality in the current social, political and economic policies has been depicted in her novels. Krishnaji has discussed the economic problem in the novel 'Yaaron Ke Yaar'. Man needs money to live. Nothing happens without money. Due to so much inflation, he was not able to fulfill his daily needs properly. In this novel, 'Bhawani Prasad' was sad due to poverty and was helpless for a job. Due to lack of money, his son dies. Bhavani Babu's life becomes miserable due to financial poverty. On the other hand, bureaucratic office environment in which officers are the owners of offices and on the other hand, the condition of clerks is pitiable. In the novel 'Ae Ladki', due to economic inequality, Sassoon had to remain unmarried throughout her life. In the novel 'Daar se Bichhudi', Pasho could not become the owner of the property. In this novel, there is no clear description of the economic condition of the people living in the village. In the novel 'Mitro Marjani', 'Mitro', even after being married, wants to grace the bed of another man every day to fulfill the economic deficiency in the joint family. She has relations with a new man every day. She sells her body to earn money and has fun and also helps her husband financially. As a result, Mitro becomes a woman of loose character. Financial problems become extremely deforming for Mitro. The novel 'Dilo-Danish' depicts the complex nature of the family life of the Indian upper middle class and middle class. In today's modern age, everyone is becoming crazy in the greed of personal freedom and personal happiness. Due to this, family relationships are deteriorating. In this novel, lawyer Kripanarayan comes in the category of upper middle class. He lives a luxurious life while living in a mansion. He lives a double life. Hence, he is financially strong. In this novel, the writer has depicted lawyer Kripanarayan as living a double life. The novel 'Zindaginama' presents the economic condition of the region of Punjab. India's economic condition could not be strengthened even at the time of independence and years after it. This novel has a special description of the upper and lower classes, middle class farmers and laborers. In this, the writer has based her novel on the economic inequality prevailing between Shahs and Jatt labourers, farmers and small-time traders to highlight the economic inequality prevailing in the region of Punjab. In this novel, women also earn money by spinning the charkha, selling vegetables, working as maids in the houses of the rich or by animal husbandry. Krishnaji has especially depicted economic corruption in her novels.